Avaliação da atividade mioelétrica dos músculos trapézio superior e deltoide médio com o uso de exoesqueleto industrial para membros superiores - Wenke, Rodney (2019)
Despite the ongoing trend of automation and mechanization in the industry, many workers are still exposed to load handling, repetitive movements and improper body postures. A typical example of the problem is the work done with the movement of the upper limbs in elevation, especially with the hands above the head, which causes the compression of the shoulder rotator cuff tendons and the reduction of the palmar grip force, causing many injuries. Irreversible times. As an option to solve the problem, the exoskeletons to the upper limbs can be indicated. Exoskeletons are functional orthoses that help the human body to perform certain tasks, dressing the body to support movements and can be classified as passive or active. Despite recent advances in the development of exoskeletons for industrial applications, these are not yet widely adopted by industry. Some of the challenges that have to be overcome are reductions in the range of some movements, misalignment between human anatomy and exoskeleton kinematics, as well as discomfort. The aim of this study was to evaluate the influence of the use of upper limb exoskeleton on the middle deltoid and upper trapezius muscles while performing shoulder abduction movements. The evaluation was performed in the laboratory and in a car assembly line and consisted of electromyographic evaluation with shoulder abduction at 90 degrees angle with and without the use of exoskeleton. Complementarily, the usability of the exoskeleton was evaluated. The data collected in both environments were processed in MATLAB software and extracted the “Root Mean Square” (RMS) of the signal. In laboratory abduction tests a mean right deltoid RMS was obtained with a significant difference of 56% (p <0.001), the right trapezius presented a mean RMS with a significant difference of 52.49% (p <0.001). In the assembly line tests we obtained for the right deltoid an average RMS with no significant difference of 0.5509% (p> 0.001) in the right trapezius. 1.7489% (p> 0.001) was not significant and the left trapezius showed a non-significant mean RMS of 0.4452% (p> 0.001). It was concluded that in assembly line tests the use of exoskeleton did not significantly reduce muscle effort in all studied muscles, except for the right trapezius, in laboratory tests the difference in muscle effort, with and without exoskeleton, was significant to the muscles studied.